2021
DOI: 10.1155/2021/5434525
|View full text |Cite
|
Sign up to set email alerts
|

Component Composition and Antimicrobial Activity of CO2 Extract of Portulaca oleracea, Growing in the Territory of Kazakhstan

Abstract: In the medicine of many countries, the use of herbal healing agents included a significant contribution to improving human health and well-being. Many antibiotics have been widely used to treat infectious diseases caused by various pathogenic bacteria. However, increased multidrug resistance has led to increased severity of diseases caused by bacterial pathogens. Bacteria remain the main causative agents of diseases that cause human death, even in the present day. This cause prompted scientists to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…It was also found hexane as a control does not show antimicrobial activity against cultures of microorganisms ( Figure 4 ). It was conditionally accepted that the diameter of the growth zone delay was over 15 mm for high activity, 10–15 mm for medium activity, and less than 10 mm for low activity [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was also found hexane as a control does not show antimicrobial activity against cultures of microorganisms ( Figure 4 ). It was conditionally accepted that the diameter of the growth zone delay was over 15 mm for high activity, 10–15 mm for medium activity, and less than 10 mm for low activity [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, this extract has a bacteriostatic effect against the clinical isolate of Staphylococcus haemolyticus and fungicidal activity against Candida albicans ATCC 10231 with a growth retardation zone of 22.0 ± 1.73. When interpreting the data, it was conditionally assumed that the diameter of the growth retardation zone of more than 15 mm proves high antimicrobial activity; 10-15 mm, average antimicrobial activity; and less than 10 mm, low antimicrobial activity [60]. e antimicrobial activity of the obtained extracts was compared with other extracts obtained by Serbian scientists Pavle Z. Mašković and others.…”
Section: Results Of Determination Of the Antimicrobial Activity Ofmentioning
confidence: 99%
“…El-Desouky et al (2021) found antifungal activities against three species of Aspergillus namely A. avus, A. ochraceus and A. parasiticus. Recently Tleubayeva et al (2021) showed that carbon dioxide extract of Purslane possess antibacterial activities against E. coli, S. aureus, B. subtilis, and antifungal activity against C. albicans.…”
Section: Antimicrobial Potentialmentioning
confidence: 99%